محمد أركون من نقد العقلانية "التراث" إلى عقلانية النقد "مشروعه النقدي" - عميرات، محمد أمين; العطار، أحمد Alattar, Ahmed (المركز الجامعي بلحاج بوشعيب عين تموشنت, 2021)
من المشاريع الفكرية والفلسفية؛ مشاريع "نقد العقل"، سواء "نقد العقل العربي" أو "نقد العقل الإسلامي"، التي حاولت أن تؤسس لنهضة حديثة عبر آليات ابستمولوجية ومفاهيمية جديدة. جسدها محمد أركون في نقد للعقلانية التراثية التي تحيا في فلك زماني من التاريخ (الماضي)؛ بتفكيك العقل العربي الإسلامي كمنهجية وعقلانية النقد كمشروع حداثي وظف فيه الإسلاميات التطبيقية كمنهج غربي حديث، لإعادة قراءة التراث الإسلامي للكشف عن أسباب توقف العقل الإسلامي وإعادة تشغيله حتى يلتحق بركب التقدم الذي يعيشه العقل الغربي.
Among the intellectual and philosophical projects, the projects of Criticism of Reason, whether critics of the Arab mental criticism or Islamic one, which attempted to establish a modern renaissance through new epistemological and conceptual mechanisms. Embodied by Muhammad Arkoun in a review of the traditional rationality that lives in a temporal orbit of history (the past) by dismantling the Arab-islamic mind as a methodology. The rationality of criticism as a modernist project in which Arkoun employ the applied Islamism as a modern Western method to re-read the Islamic heritage in order to reveal the reasons to stop the Islamic mind and restart it until it joins the progress of the Western mind.
Keywords: أركون، محمد -- النقد الأدبي -- التراث العربي -- المجتمعات الإسلامية